Experimental modeling of changes in geomechanical parameters of reservoir rock during water flooding operations - Mahmoud Abedifar; Seyed Jamal Sheikh Zakariaei; Mohammad Abdideh; Shahin Kord; Mastaneh Hajipour (Scientific Reports)
Abstract Reservoir geomechanical modeling is considered one of the important parts of the research accomplished on planning oil and gas fields’ exploitation and drilling. The present research aimed at investigating the changes of geomechanical elastic coefficients and in-situ stress field before and after water flooding in carbonate reservoirs of Asmari reservoir of Ahvaz oil field in southwest Iran. The results reveal changes in geomechanical parameters before and after the water flooding process. Specifically, Young’s modulus decreased from 21 to 18 GPa, while it increased from 14.22 to 23.77 GPa due to the flooding process and an increase in temperature from 25 to 75 °C. Likewise, the friction coefficient has increased from 32.21 (before the water flooding process) to 38.53 (after the mentioned process). Similarly, the bulk modulus before the flooding process decreased from 12.23 to 10.27 GPa after the flooding process. In addition, increasing the temperature from 25 to 75 °C after the flooding process caused an increase in the bulk coefficient from 8.4 to 12.7 GPa.Similarly, the changes in the shear modulus before the flooding process decreased from 8.67 to 7.7 GPa after flooding. Moreover, an increase in temperature from 25 to 75 °C caused an increase in shear modulus from 5.8 to 9.9 GPa. Furthermore, examining the changes in Mohr’s circles before and after the flooding process by water fluid showed that these circles will change.